Physico-Chemical Characteristics of Dates Palm Sheet Jam (Phoenix Dactylifera L.) with Variations of Jackfruit Dami Pectin Extracts and CMC (Carboxymethyl Cellulose) - Suci Apriantika; Titisari Juwitaningtyas (Agroindustrial Technology Journal, 2024)
Sheet jam is a semi-solid form of jam, printed in a size that is adjusted to the size of white bread in general so that it makes it easier for users to serve food. Making sheet jam requires fruit that contains pectin to produce a good jam texture, one of which is dates. The pectin content in dates is low to form sheet jam, so it is necessary to add gelling ingredients from natural pectin such as jackfruit dami with a pectin content of 11.69%. The type of commercial pectin used is CMC (carboxymethyl celulose). The aims of the research were to determine the effect of variations in Jackfruit Dami extract and CMC on the physico-chemical characteristics and organoleptic acceptability of date palm jam. The research was designed using a Completely Randomized Design (CRD) with one factor, namely the concentration of Jackfruit Dami pectin treatment and CMC F1 (1% : 0%), F2 (0.6% : 0.4%), F3 (0.5% : 0 .5%), F4 (0.4% : 0.6%), F5 (0% : 1%). The parameters in this research were organoleptic tests (color, taste, aroma, texture and overall), water content, pH, texture and color. Statistical analysis used One Way Analysis of Variance (ANOVA) followed by the DMRT test. The results of the analysis showed that the formulation of date palm jam had a significant effect on the physico-chemical properties including water content (31.11% - 34.22%), pH (3.97 - 4.32), adhesiveness (30.03 Nmm - 13 .38 Nmm), cohesiveness (0.83 – 0.38), hardness (78.59 N – 16.17 N), color L* (34.48 – 40.37), color a* (4.72 – 1, 42), and color b* (19.31 – 27.13). Organoleptic acceptance test results showed that the sample preferred by the panelists was F3 with the addition of 0.5% Jackfruit Dami pectin and 0.5% CMC.